Bacterium-conductive macromolecular copolymer heterozygote as well as preparation method and application thereof

By constructing bacteria-conductive polymer copolymer hybrids, the problem of low electrocatalytic performance in microbial fuel cell systems is solved, and efficient electron transfer and significantly improved electrical production performance are achieved.

CN119752703APending Publication Date: 2025-04-04RES CENT FOR ECO ENVIRONMENTAL SCI THE CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411923509.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The electrocatalytic performance of microbial fuel cell systems is mainly due to the poor ability of electroactive microorganisms to form biofilms on the surface of electrode materials, which leads to low loading of microbial electrocatalysts and the outer membrane of microbials is not conductive, resulting in low electron transfer efficiency.

Method used

Through live cell surface engineering technology, a bacterial-conductive polymer copolymer hybrid is constructed. The hybrid has both viscosity and high conductivity and can be used as a bioelectrocatalyst in microbial fuel cell systems. The method includes inoculating and culturing bacteria, adsorbing trivalent ions on the surface, and oxidizing reactions in a reaction system containing conductive polymer monomer and dopamine hydrochloride to form a bacteria-conductive polymer copolymer hybrid.

Benefits of technology

The electrode load and electron transfer efficiency of the microbial fuel cell system are improved, the output power density is as high as 5.02 watts/square meter and the maximum current density is as high as 14.18 amperes/square meter, which is an order of magnitude higher than the output performance of unmodified bacteria.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005208636960000011
    Figure HDA0005208636960000011
  • Figure HDA0005208636960000012
    Figure HDA0005208636960000012
  • Figure HDA0005208636960000013
    Figure HDA0005208636960000013
Patent Text Reader

Abstract

The invention discloses a bacterium-conductive macromolecular copolymer heterozygote as well as a preparation method and application thereof. The preparation method comprises the following steps: 1) inoculating bacteria into an LB culture solution for culture, centrifuging the obtained bacterial solution, collecting thalli, washing with deionized water, and centrifuging to obtain thalli; 2) re-suspending the thalli in a ferric iron salt aqueous solution, oscillating, centrifuging, and washing to obtain thalli with ferric iron ions adsorbed on the surfaces; and (3) resuspending and reacting the thalli with the ferric ions adsorbed on the surfaces in a reaction system containing a conductive polymer monomer and dopamine hydrochloride, adding an oxidizing agent, adjusting the pH value of the reaction system to be alkaline so as to carry out oxidation reaction, centrifuging after the reaction, washing with deionized water, and centrifuging again, thereby obtaining the bacterium-conductive macromolecular copolymer heterozygote. The preparation method disclosed by the invention is simple, and the bacterium-conductive macromolecular copolymer hybrid can be applied to a microbial fuel cell system as a bioelectrocatalyst with viscosity and high conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the cross field of biotechnology and materials, and relates to a bacteria-conductive polymer copolymer hybrid and a preparation method and application thereof. Background Art

[0002] Energy and environmental issues are two major issues facing the world as human society develops today. Fossil energy reserves are limited and non-renewable. As they are mined and used, energy shortages and environmental pollution problems are becoming increasingly prominent. The development and utilization of clean energy can help solve the above problems, so it is of great significance. Microbial fuel cells (MFCs) are a new type of fuel cell technology that uses microorganisms as electrocatalysts to convert chemical energy in organic matter into electrical energy. They can be widely used in clean energy production, electrochemical sensing, sewage treatment, high value-added product electrosynthesis and other fields, and have the advantages of clean, environmentally friendly, low cost and sustainability.

[0003] However, the electrocatalytic performance of current microbial fuel cell systems is much lower than that of chemical fuel cell systems. There are two main reasons for this: first, many electroactive microorganisms have poor ability to form biofilms on the surface of electrode materials and are not easy to attach and grow on the electrodes, resulting in a low loading of microbial electrocatalysts on the electrode surface; second, the outer membrane of microorganisms is not conductive, resulting in large resistance losses in the process of electron transfer from the biofilm to the electrode, and low efficiency of electron transfer between microorganisms and electrodes.

[0004] In order to solve the above problems, a lot of research in the past has focused on the modification of electrode materials, but this method cannot solve the problem of microbial cell membranes not being conductive. The disadvantage is particularly obvious when the biomass enriched on the electrode is large, and the electrons generated by a large number of cells growing inside the cell cluster (biofilm) cannot be effectively transferred to the outside to reach the electrode. Therefore, it is urgent to develop new methods that can simultaneously solve the two problems of low microbial loading on the electrode surface and non-conductive biofilm.

[0005] Living cell surface engineering refers to an emerging technology that uses physical or chemical methods to grow biocompatible materials on the cell surface, giving cells new functions without affecting cell survival. It is currently mainly used in the fields of biomedicine, biocatalysis, bioelectronics, etc. Through cell surface modification, the material not only brings new functions to the cells, but its outer coating structure can also enhance the ability of cells to resist adverse external environments. Therefore, it is urgent to construct a new type of bacteria-conductive polymer copolymer hybrid that is both sticky and highly conductive. Summary of the invention

[0006] The purpose of the present invention is to provide a bacteria-conductive polymer copolymer hybrid and its preparation method and application. The bacteria-conductive polymer copolymer hybrid of the present invention has a simple preparation method based on living cell surface engineering technology, and the bacteria-conductive polymer copolymer hybrid has both viscosity and high conductivity, and can be used as a bio-electrocatalyst with viscosity and high conductivity in a microbial fuel cell system.

[0007] The present invention provides a method for preparing a bacteria-conductive polymer copolymer hybrid, comprising the following steps:

[0008] 1) Inoculate the bacteria into LB culture medium, centrifuge the obtained bacterial solution to collect the bacterial cells, wash them with deionized water, and centrifuge them to obtain the bacterial cells;

[0009] 2) resuspending the bacterial cells obtained in step 1) in a trivalent iron salt aqueous solution, shaking, centrifuging, and washing to obtain bacterial cells with trivalent iron ions adsorbed on the surface;

[0010] 3) The bacteria with trivalent iron ions adsorbed on the surface obtained in step 2) are resuspended and reacted in a reaction system containing a conductive polymer monomer and dopamine hydrochloride, and then an oxidant is added and the pH of the reaction system is adjusted to alkaline to perform an oxidation reaction. After the reaction, the mixture is centrifuged, washed with deionized water, and centrifuged again to obtain a bacteria-conductive polymer copolymer hybrid.

[0011] In the above method, in step 1), the bacteria is selected from at least one of Shewanella putrefaciens, Shewanella oneidensis and Shewanella loihica; specifically, it may be at least one of Shewanella putrefaciens CN-32, Shewanella oneidensis MR-1 and Shewanella loihica PV-4.

[0012] In the above method, in step 2), the trivalent iron salt is any one of ferric nitrate, ferric chloride, and ferric citrate;

[0013] The bacterial cells are resuspended in an aqueous solution of ferric iron salt, wherein the final concentration of the ferric iron salt may be 1-20 mM, specifically 15 mM, 1-15 mM, 15-20 mM or 10-20 mM.

[0014] In the above method, in step 2), the oscillation time may be 20 to 60 minutes, specifically 40 minutes, and the rotation speed may be 60 to 200 rpm, specifically 100 rpm, 60 to 100 rpm, or 100 to 200 rpm.

[0015] In the above method, in step 3), the monomer of the conductive polymer is selected from at least one of pyrrole, aniline and thiophene;

[0016] The concentration of the conductive polymer monomer in the reaction system may be 3.15 to 12.68 mM, specifically 12.68 mM;

[0017] The concentration of dopamine hydrochloride in the reaction system may be 0.4032-0.8064 mM, specifically 0.4032 mM;

[0018] The reaction time in the reaction system containing the conductive polymer monomer and dopamine hydrochloride may be 1.5 to 5 minutes, specifically 2 minutes, 1.5 to 2 minutes, 2 to 5 minutes or 1.5 to 3 minutes.

[0019] In the above method, in step 3), the oxidant is selected from at least one of ammonium persulfate, sodium persulfate and potassium persulfate;

[0020] The concentration of the oxidant in the reaction system may be 1.45 to 2.9 mg / ml, specifically 1.45 mg / ml;

[0021] The pH of the reaction system is adjusted by a pH adjuster, and the pH adjuster is tris (hydroxymethylaminomethane) (Tris) buffer and / or sodium hydroxide; the pH of the reaction system is adjusted to an alkaline pH of 8.5 to 13.5, specifically 8.5.

[0022] In the above method, in step 3), the conditions of the oxidation reaction are as follows: temperature 8-30° C., rotation speed 60-200 rpm, and time 5-23 h.

[0023] The present invention also provides the bacteria-conductive polymer copolymer hybrid prepared by the above method.

[0024] The bacteria-conductive polymer copolymer hybrid of the present invention is used in preparing microbial fuel cells.

[0025] In the present invention, the bacteria-conductive polymer copolymer hybrid is used as a bio-electrocatalyst with viscosity and high conductivity in the preparation of microbial fuel cells.

[0026] The present invention has the following beneficial effects:

[0027] 1. The preparation method of the present invention is simple to operate, green and economical, the reaction process is biocompatible, the reaction system is non-toxic, and has no significant effect on the activity of microbial cells. It does not require complex and expensive equipment and can be prepared on a small scale in the laboratory or scaled up in the factory.

[0028] 2. This method has no restrictions on the types of microorganisms. The constructed bacteria-conductive polymer copolymer hybrid gives the microorganisms new functions: viscosity and high conductivity without affecting the original functions of the microorganisms.

[0029] 3. After the bacteria-conductive polymer copolymer hybrid constructed by the present invention is applied to the microbial fuel cell system, the electrode load is large, the extracellular electron transfer efficiency is high, and the external output power density is as high as 5.02 watts / square meter, which is an order of magnitude higher than the output power density of 0.51 watts / square meter of unmodified bacteria, and the maximum current density is as high as 14.18 amperes / square meter, which is 3.96 times higher than the maximum current density of 3.58 amperes / square meter of unmodified bacteria. The bacteria-conductive polymer copolymer hybrid can be used as an excellent microbial electrocatalyst to greatly improve the power generation performance of microbial fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a field emission scanning electron micrograph of the bacteria-conductive polymer copolymer hybrid prepared in Example 1 of the present invention.

[0031] Figure 2 This is a field emission transmission electron micrograph of the bacteria-conductive polymer copolymer hybrid prepared in Example 1 of the present invention.

[0032] Figure 3 Graphs showing the viscosity of bacteria-conductive high molecular polymer hybrids prepared in Examples 1 to 3 of the present invention.

[0033] Figure 4 Graphs showing the conductivity of bacteria-conductive high molecular polymer hybrids prepared in Examples 1 to 3 of the present invention.

[0034] Figure 5 The conductivity diagram of the bacteria-conductive high molecular polymer hybrid prepared in Examples 3 to 4 of the present invention; wherein bacteria@polydopamine is the hybrid prepared in Example 3, and bacteria@polypyrrole@polydopamine is the hybrid prepared in Example 4.

[0035] Figure 6 Polarization curves and output power density diagrams of the bacteria-conductive high molecular polymer hybrids prepared in Examples 1 to 3 of the present invention after being loaded into a microbial fuel cell system. DETAILED DESCRIPTION

[0036] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0037] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0038] The present invention is further described in detail below by specific examples, so as to better understand the technical connotation of the present invention, but the embodiments of the present invention are not limited thereto. The examples provided below can be used as a guide for further improvement by ordinary technicians in the field of the present invention, and do not constitute a limitation of the present invention in any way.

[0039] In the following examples, the source of Shewanella putrefaciens CN-32 is referenced from the following literature: Le Tao; Xin Wang; Boosting microbial electrocatalysis via localized high electron shuttles concentration by monolithic electrode based on nanostructured nitrogen-doped carbon microtubes, Journal of Power Sources, Volume 514, 230557-230564.

[0040] Embodiment 1:

[0041] A method for preparing a bacteria-conductive polymer copolymer hybrid having both viscosity and high conductivity comprises the following steps:

[0042] (1) Shewanella putrefaciens CN-32 was inoculated into LB culture medium, the LB culture medium composition was 10 g / L tryptone, 10 g / L sodium chloride, and 5 g / L yeast extract; the volume ratio of the inoculum to the LB culture medium was 1:100, the culture temperature was 30°C, the shaking speed was 120 rpm, the culture time was 20 h, and the obtained bacterial solution was centrifuged to collect the bacterial cells, washed with deionized water, and centrifuged;

[0043] (2) resuspending the bacterial cells obtained in step (1) in an aqueous solution of ferric nitrate (the final concentration of the aqueous solution of ferric nitrate is 15 mM), shaking for 30 min at a speed of 200 rpm, centrifuging, and washing to obtain bacterial cells with trivalent iron ions adsorbed on the surface;

[0044] (3) The bacteria with trivalent iron ions adsorbed on the surface obtained in step (2) are resuspended in a reaction system containing pyrrole monomer and dopamine hydrochloride (the monomer concentration in the reaction system is 12.68 mM, and the dopamine hydrochloride concentration is 0.4032 mM). After reacting for 2 minutes, the oxidant ammonium persulfate (the concentration in the system is 1.45 mg / ml) is added and the pH of the reaction system is adjusted to alkaline (8.5) with tris(hydroxymethyl)aminomethane (Tris) for further reaction. The reaction is stirred or shaken at a speed of 200 rpm. After fully reacting at 8° C. for 23 hours, the mixture is centrifuged, washed with deionized water, and centrifuged again to obtain a bacteria-conductive polymer copolymer hybrid having both viscosity and high conductivity, which is recorded as bacteria@polypyrrole-polydopamine copolymer.

[0045] like Figure 1 Field emission scanning electron microscopy images of the hybrid Figure 2 As shown in the field emission transmission electron microscopy image of the hybrid, it can be clearly seen that the conductive polymer copolymer with granular wrinkles grows on the surface of the bacteria. Figure 3 As shown in Figure 2, the viscosity of the bacteria-conductive polymer copolymer hybrid was greatly increased, which was more than 42 times that of the naked bacteria without copolymer growth on the surface. Figure 4 As shown in the figure, the naked bacteria cell membrane is not conductive, while the conductivity of the bacteria-conductive polymer copolymer hybrid is greatly increased, 2145 times that of the naked bacteria, which can greatly promote extracellular electron transfer and is conducive to electrical respiration. Figure 6 As shown, the bacteria-conductive polymer copolymer hybrid is loaded in the microbial fuel cell system. The microbial fuel cell system includes an anode chamber and a cathode chamber, each with a volume of 100 ml. The anode chamber is filled with M9 culture solution, with the ingredients: 3g / LKH2PO4, 0.5g / L NaCl, 6.78g / L Na2HPO4, 1g / LNH4Cl, 1mM MgSO4, 0.1mM CaCl2, and the cathode chamber is filled with cathode liquid, with the ingredients: 50mM K3[Fe(CN)6], 50mMK2HPO4, 50mM KH2PO4, carbon felt as anode, carbon brush as cathode, and the hybrid grows on carbon felt. The external output power density is as high as 5.02 watts / square meter, which is an order of magnitude higher than the power density of 0.51 watts / square meter output by bare bacteria, and the maximum current density is as high as 14.18 amperes / square meter, which is 3.96 times higher than the maximum current density of 3.58 amperes / square meter output by bare bacteria.

[0046] Comparative Example 1:

[0047] Comparative Example 1 is basically the same as Example 1, but with the following changes: in step (3), the reaction system does not contain dopamine hydrochloride; the pH value of the reaction system does not need to be adjusted to alkaline, and the obtained product is recorded as bacteria@polypyrrole.

[0048] The viscosity of the hybrid Figure 3 As shown, it is 6.9 times that of naked bacteria. Figure 4 As shown in Figure 2, it is 396 times that of naked bacteria. After loading into the microbial fuel cell system, Figure 6 As shown, the external output power density is 2.46 W / m2, which is 4.82 times that of naked bacteria, and the maximum current density is as high as 8.86 A / m2, which is 2.47 times that of naked bacteria.

[0049] By comparing the results in Example 1 with those in Comparative Example 1, it can be seen that since the polypyrrole-polydopamine copolymer contains catechol groups, it has viscosity, and the viscosity helps the prepared bacteria @ polypyrrole-polydopamine copolymer hybrid to adhere and grow on the electrode surface; at the same time, the copolymerization of the two can improve the conductivity of the conductive polymer polypyrrole, which is beneficial to the improvement of the electrocatalytic performance of the microbial electrocatalyst; the combined effect of these two factors leads to the microbial fuel cell system loaded with the bacteria @ polypyrrole-polydopamine copolymer obtained in Example 1, which has better performance than the microbial fuel cell system loaded with the bacteria @ polypyrrole obtained in Comparative Example 1.

[0050] Comparative Example 2:

[0051] Comparative Example 2 is basically the same as Example 1, but with the following changes: In step (3), the reaction system does not contain a conductive polymer monomer, and the obtained product is recorded as bacteria@polydopamine.

[0052] The viscosity of the hybrid Figure 3 As shown, it is 9.66 times that of naked bacteria. The conductivity is Figure 4 As shown in Figure 2, it is 2.41 times that of naked bacteria. After loading into the microbial fuel cell system, Figure 6 As shown, the external output power density is 1.73 W / m2, which is 3.39 times that of naked bacteria, and the maximum current density is as high as 5.82 A / m2, which is 1.63 times that of naked bacteria.

[0053] By comparing the results in Example 1 with those in Comparative Example 2, it can be seen that although polydopamine is rich in catechol groups and has a certain viscosity, which is conducive to the attachment and growth of the prepared bacteria @ polydopamine on the electrode; but its conductivity is very weak. Therefore, although the electrocatalytic performance of the prepared bacteria @ polydopamine hybrid is improved compared with that of naked bacteria, it is still relatively weak, not only lower than the bacteria @ polypyrrole-polydopamine hybrid of the present invention, but also lower than the bacteria @ polypyrrole hybrid.

[0054] Comparative Example 3:

[0055] Comparative Example 3 is basically the same as Example 1, but with the following changes: In step (3), no oxidant is added to the reaction system, and the obtained product is recorded as bacteria@polypyrrole@polydopamine. Figure 5 As shown, it is 2.45 times that of naked bacteria.

[0056] By comparing the results in Example 1 with those in Comparative Example 3, it can be seen that during the preparation of the hybrid, although the trivalent iron adsorbed on the surface of the bacterial cell membrane has a certain oxidizing property, it can only oxidize the monomers in direct contact with it. As the reaction continues, the bacterial cell membrane is completely wrapped, and the subsequent monomers cannot contact the trivalent iron on the surface of the cell membrane. After that, the oxidative polymerization of the monomers will not proceed. At this time, the hybrid will be coated with weakly conductive polydopamine, and the resulting product is bacteria @ polypyrrole @ polydopamine, which has a conductivity comparable to that of bacteria @ polydopamine, that is, lower than the bacteria @ polypyrrole-polydopamine hybrid of the present invention. In summary, this illustrates the importance of adding an additional oxidant to the bulk solution during the reaction process of preparing the hybrid.

[0057] The above embodiments are only specific examples of the present invention, which are used to illustrate the detailed preparation method, composition and application of the hybrid in the present invention, and are not intended to limit the present invention. Without departing from the essential content of the present invention, any improvement, substitution or modification made by those skilled in the art shall fall within the scope of protection of the present invention.

Claims

1. A method for preparing a bacteria-conductive polymer copolymer hybrid, characterized in that: The steps include: 1) Inoculate the bacteria into LB culture medium, centrifuge the obtained bacterial solution to collect the bacterial cells, wash them with deionized water, and centrifuge them to obtain the bacterial cells; 2) resuspending the bacterial cells obtained in step 1) in a trivalent iron salt aqueous solution, shaking, centrifuging, and washing to obtain bacterial cells with trivalent iron ions adsorbed on the surface; 3) The bacteria with trivalent iron ions adsorbed on the surface obtained in step 2) are resuspended and reacted in a reaction system containing a conductive polymer monomer and dopamine hydrochloride, and then an oxidant is added and the pH of the reaction system is adjusted to alkaline to perform an oxidation reaction. After the reaction, the mixture is centrifuged, washed with deionized water, and centrifuged again to obtain a bacteria-conductive polymer copolymer hybrid.

2. The method according to claim 1, characterized in that In step 1), the bacteria is selected from at least one of Shewanella putrefaciens, Shewanella oneidensis and Shewanella loihica.

3. The method according to claim 1 or 2, characterized in that: In step 2), the trivalent iron salt is any one of ferric nitrate, ferric chloride, and ferric citrate; The bacterial cells are resuspended in a trivalent iron salt aqueous solution, and the final concentration of the trivalent iron salt is 1-20 mM.

4. The method according to any one of claims 1 to 3, characterized in that In step 2), the shaking time is 20 to 60 minutes, and the rotation speed is 60 to 200 rpm.

5. The method according to any one of claims 1 to 4, characterized in that In step 3), the monomer of the conductive polymer is selected from at least one of pyrrole, aniline and thiophene; The concentration of the conductive polymer monomer in the reaction system is 3.15 to 12.68 mM; The concentration of dopamine hydrochloride in the reaction system is 0.4032-0.8064 mM; The reaction time in the reaction system containing the conductive polymer monomer and dopamine hydrochloride is 1.5 to 5 minutes.

6. The method according to any one of claims 1 to 7, characterized in that In step 3), the oxidant is selected from at least one of ammonium persulfate, sodium persulfate and potassium persulfate; The concentration of the oxidant in the reaction system is 1.45-2.9 mg / ml; The pH of the reaction system is adjusted by using a pH adjuster, and the pH adjuster is tris(hydroxymethyl)aminomethane buffer and / or sodium hydroxide; the pH of the reaction system is adjusted to an alkaline pH of 8.5 to 13.

5.

7. The method according to any one of claims 1 to 6, characterized in that In step 3), the conditions of the oxidation reaction are as follows: temperature 8-30° C., rotation speed 60-200 rpm, and time 5-23 h.

8. The bacteria-conductive polymer copolymer hybrid prepared by the method according to any one of claims 1-7.

9. Use of the bacteria-conductive polymer copolymer hybrid according to claim 8 in the preparation of a microbial fuel cell.

10. The use according to claim 9, characterized in that: The bacteria-conductive polymer copolymer hybrid is used as a bio-electrocatalyst in the preparation of microbial fuel cells.